Photocatalytic Degradation of Toluene in Air Using a Fluidized Bed Photoreactor - O. Prieto; J. Fermoso; R. Irusta (International Journal of Photoenergy)
The photocatalytic degradation of toluene in air was carried out on particles of TiO2 in a photocatalytic reactor that had been developed to study the treatment of organic pollutants in a gaseous phase. Hypothetically, the fluidized bed technology of this reactor could make it possible to increase the mass transfer coefficients in comparison with those of conventional photoreactors. The photocatalytic particles used were prepared by mixing TiO2 (Degussa P25) and starch in a methanol solution. The XRD and SEM results of these aggregates confirm the titanium dioxide (Degussa P25) characteristics, such as the presence of anatase on the particle surface and spongy and wrinkled morphology. Toluene concentrations varied from 0.9 to 199 ppmv, and all the experiments were carried out with a flow rate of 300 NL/h. Toluene conversions from 77% to 100% were obtained in the range studied. In this work, the regeneration processes of deactivated TiO2 photocatalysts have been investigated using FT-IR and GC/MS techniques. Benzoic acid, benzaldehyde, and benzyl alcohol were the three major intermediate products identified.